2022
DOI: 10.3390/antiox11101919
|View full text |Cite
|
Sign up to set email alerts
|

The Status of Oxidative Stress in Patients with Alcohol Dependence: A Meta-Analysis

Abstract: Alcohol-induced oxidative stress (OS) plays a pivotal role in the pathophysiology of alcohol dependence (AD). This meta-analysis was aimed at investigating the changes in the levels of OS biomarkers in AD patients. We included relevant literature published before 1 April 2022, from the PubMed, Web of Science, and EBSCO databases following PRISMA guidelines. Finally, 15 eligible articles were enrolled in this meta-analysis, including 860 patients and 849 controls. Compared with healthy controls, AD patients had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 132 publications
0
5
0
1
Order By: Relevance
“…Early detection and monitoring of molecular mechanisms leading to alcohol impairment of cognitive functions remain a major challenge for predictive diagnosis and prognosis in clinical practice. In this regards, oxidative stress and inflammation are key underlying mechanisms in the brain that can be explored to identify stress biomarkers capable of predicting cognitive dysfunctions in patients with AUD [ 9 , 10 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early detection and monitoring of molecular mechanisms leading to alcohol impairment of cognitive functions remain a major challenge for predictive diagnosis and prognosis in clinical practice. In this regards, oxidative stress and inflammation are key underlying mechanisms in the brain that can be explored to identify stress biomarkers capable of predicting cognitive dysfunctions in patients with AUD [ 9 , 10 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanisms by which alcohol activate innate immune signaling and oxidative stress affecting cognitive functions are partially understood, despite the remarkable ability of alcohol to activate the Toll-like receptor (TLR) 4 directly [ 9 , 10 , 11 , 12 ]. Alcohol toxicity-induced oxidative stress and inflammation in the brain lead to neuronal cell death (intracellular damage and apoptosis) and impaired neuronal function (e.g., mitochondrial dysfunction), caused by the release of neuroimmune signaling, such as high-mobility group box 1 (HMGB1), as well as the accumulation of reactive oxygen and nitrogen species (ROS/RNS) and toxic protein aggregates, including advanced glycation end-products (AGEs) [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The exact teratogenic mechanism of alcohol on fetal development is still unclear. EtOH contributes to the malfunctioning of the neurological system in children exposed in utero by decreasing glutathione peroxidase action, with an increase in the production of ROS [ 30 , 31 , 61 ]. It causes oxidative stress and the oxidation of polyunsaturated fatty acids with the formation of aldehyde toxicants [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Upon admission to the hospital, we performed an ultrasound exam with evidence of reduced amniotic fluid (amniotic fluid index—AFI: 73 mm) and an estimated fetal weight of 1559 g, equal to the first percentile (z-score −3.303) for gestational age [ 29 , 30 , 31 ]. Fetal Doppler showed an umbilical artery pulsatility index (PI) of 1.23, equal to the 96th percentile (z-score 1.697), middle cerebral artery PI of 1.62, equal to the 16th percentile (z-score −0.995), with the cerebroplacental ratio of 1.32, equal to the 3rd percentile (z-score −2.004) for gestational age.…”
Section: Case Reportmentioning
confidence: 99%
“…emphasized the crucial roles of aberrant histone deacetylase 2-mediated histone modifications and synaptic plasticity within the AMY in the pathogenesis of AUD [114]. It has been widely reported that biological processes such as oxidative stress, GABAergic neurotransmission and neuroimmune were strongly related to the onset and progression of AUD [115][116][117]. Nevertheless, there is still a lack of research on the relationships between ncRNAs and genetic and epigenetic mechanisms, as well as the possible involvement of ncRNAs-mediated cellular functions and biological processes in the course of AUD.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%